Division of Inheritance of Heirs of Different Religions with Heirs According to the Compilation of Laws: Pembagian Warisan Antara Ahli Waris Beragama Berbeda dengan Ahli Waris Menurut Kompilasi Hukum - Mat Hasan; Moh. Muhibbin; Diyan Isnaeni (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Inheritance remains one of the most sensitive issues in Islamic family law, as it intertwines material distribution with justice, kinship, and social harmony. Specific Background: The Compilation of Islamic Law (KHI) in Indonesia explicitly prohibits inheritance across religions, creating legal rigidity when confronted with plural family realities shaped by interfaith marriages and conversions. Knowledge Gap: While classical jurisprudence closes the door to interfaith inheritance, Indonesian legal pluralism and social justice demands reveal tensions between strict fiqh norms and societal needs, with limited scholarly synthesis on the role of mandatory wills as a legal compromise. Aims: This study aims to analyze the legal construction of inheritance for heirs of different religions under the KHI and evaluate the jurisprudential role of mandatory wills as a middle path in Indonesian courts. Results: Findings show that although the KHI normatively restricts inheritance to Muslims, jurisprudence recognizes mandatory wills as a mechanism to grant non-Muslim heirs a share, aligning with constitutional principles of justice and reducing family conflict. Novelty: This research highlights mandatory wills as a dynamic legal innovation that bridges classical fiqh with contemporary demands of pluralism and human rights. Implications: Reforming inheritance law to formally integrate mandatory wills will strengthen legal certainty, prevent discrimination, and promote social harmony within Indonesia’s diverse society.Highlight : KHI prohibits interfaith inheritance but raises justice issues. Obligatory wills act as a middle ground in court practices. Reform of inheritance law is needed to be more inclusive and responsive. Keywords : Compilation of Islamic Law, Inheritance, Different Religions, Obligatory Wills, Legal Pluralism